Three Essays on Health and Pension Economics - Zhang, Xue (My University, 2017)
This thesis comprises two essays in health economics and one on pension economics. The first two essays use the institutional changes (mainly physician payment changes) of primary care reform in Ontario to study the impact of financial incentives on physician behavior and continuity of care. Specifically, we focus on two major primary care physician/General Practitioner (GP) payment model transitions in the reform: from traditional fee-for-service (FFS) to the enhanced FFS (referred as the first transition), and from enhanced FFS to blended capitation (referred to as the second transition). The first essay uses the second transition as a quasi-natural experiment and explores how the payment structure in the blended capitation model influences the provision of health care services by GPs and their practice groups. The second essay uses the first and second transitions to examine the association between continuity of care and patient rostering that is incentivized by premiums and bonuses in the enhanced FFS and the blended capitation model. The last chapter diverges from this topic and addresses one aspect of social insurance, namely pensions in China; it assesses how internal migrants and locals differ in terms of the pension contributions they make and the benefits they receive under the national policies that were recently introduced to reduce the fragmentation of the pension operations.The first chapter examines the switch in physician payment system from FFS to the blended capitation-FFS model on GPs’ billing behavior within a group practice. There are multiple dimensions of payment blending in the blended capitation model: first, a blend of capitation for services inside the capitated basket, which are quite commonly employed and represent a large proportion of the services offered by GPs, and FFS for services outside the basket; second, a blend of capitation and less than full-cost FFS payment for services inside the capitated basket; third, a blend of different payment mechanisms for rostering and non-rostering patients funded under blended capitation or traditional FFS ; fourth, a blend of pay for performance, capitation and FFS (Sweetman and Buckley, 2014). We provide both a theoretical model examining the provision of care inside and outside the capitated basket and an associated econometric analysis using comprehensive administrative data, and the second transition in primary care reform as a quasi-natural experiment. We construct a panel of continuously rostered patient-GP pairs and employ a propensity score weighted difference-in-differences approach to identify the impact of a change in the GPs’ remuneration model on the shifting of services across payment categories which are created by multiple blending dimensions. Consistent with the theory presented, rostering GPs provide fewer capitated services and simultaneously more FFS services. Other GPs within the rostering group reduce service provision within the capitated basket, with no change in FFS services. All other GPs in Ontario have relative reductions, both inside and outside the basket, which is consistent with GPs concentrating their primary care with rostered patients as a result of the introduction of the capitation payment model. The second chapter examines the impact of rostering on continuity of care, as measured indirectly by various indices, from both patients' and GPs' perspectives. The empirical analysis consists of two transitions, and three payment models with different ‘levels’ of rostering: traditional FFS has no rostering; enhanced FFS is termed as ‘weak’ rostering; blended capitation is termed ‘strong’ rostering. Estimation using propensity score weighted difference-in-differences with fixed effects is used in both transitions to identify the impacts of different ‘levels’ of rostering. Our results show that the strong patient rostering indeed strengthens the bond between patients and GPs in the second transition. Furthermore, GPs in the blended capitation model can also be combined with interdisciplinary teams to form Family Health Teams (FHTs). The FHT model performs better than the blended capitation model alone in keeping rostered patients within the rostering practice. However, we don’t find a significant increase of the continuity of care indices in the first transition, which is probably due to the rostering incentives behind enhanced FFS. The third chapter examines how the recent reforms to improve pension portability affect the relative pension treatment of migrants compared to locals in China. Using simulation methods, we compare how residents who differ in terms of their hukou, a record of household residence registration, and in their productive characteristics and geographic locations are treated by the pension system in one municipality. Shenzhen in the province of Guangdong is chosen as a representative developed urban city in China. Our results show that, even after recent reforms, migrants fare poorly compared to locals with hukou; migrants who transfer to another urban pension plan are likely to experience larger reductions in benefits than migrants who retired and remained in Shenzhen; the least benefits go to migrants who have contributed to urban plans for less than 15 years and hence have coverage only under the County and Rural Residents’ Plan. We also find that the pension replacement rate is inversely associated with income level and positively associated with the age of retirement.